The relation of heavy or prolonged bleeding during the menopause transition to risk of hysterectomy - Siobán D. Harlow; Michelle M. Hood; Alain Mukwege; John F. Randolph; Ellen B. Gold; Michael R. Elliott; Alaina C. White; Gail A. Greendale (Women's Health)
Background: During the menopause transition, one in three women experiences abnormal uterine bleeding. Few studies have evaluated the probability of hysterectomy associated with abnormal uterine bleeding during the menopause transition. Objectives: To estimate the risk of hysterectomy associated with abnormal uterine bleeding, specifically prolonged or heavy menstrual bleeding, during the menopause transition. Design: Prospective cohort study Methods: We used data collected in the Study of Women’s Health Across the Nation, a community-based, longitudinal cohort that followed women from pre- to post-menopause. It includes 1200 White (45.4%), Black (15.4%), Japanese (20.8%), and Chinese (18.4%) women, from three study sites that participated in a sub-study and provided at least 1 year of prospectively recorded menstrual calendars. Calendars ascertained bleeding days, menstrual interference with life in four domains (work, daily life, sexual life, and relationships), menopausal hormone therapy, and smoking. At baseline and 12 annual follow-up visits, information on surgeries, body mass index, pelvic pain, and socio-demographic characteristics was obtained. Multivariable Cox proportional hazard models were used to assess the relationships of hysterectomy with prolonged menstrual bleeding, heavy menstrual bleeding, and covariates. Results: Women who reported prolonged menstrual bleeding had an elevated hazard of hysterectomy (hazard ratio = 2.35, 95% confidence interval = 1.20–4.61), adjusting for pelvic pain, hormone use, and race/ethnicity; hazard ratios were attenuated after adjusting for life interference. The association of heavy menstrual bleeding with hysterectomy was not statistically significant (hazard ratio = 1.34, 95% confidence interval = 0.42–4.30). The adjusted hazard ratio for hysterectomy increased 1.5-fold for each domain in which bleeding interfered with a woman’s life. Pelvic pain, hormone therapy, and Black race were also significant predictors of hysterectomy risk. Conclusion: Prolonged menstrual bleeding during the menopause transition, particularly when accompanied by interference in one or more domains of a woman’s life, increased the risk of hysterectomy. Counseling women about non-surgical therapeutic options, and estimating the proximity of menopause, may mitigate against this increased risk.